Insight into niche separation of Risso's dolphin (Grampus griseus) in the southwestern South Atlantic via d13C and d15N values - Riccialdelli, Luciana; Newsome, Seth Darnaby; Prosser Goodall, Rae Natalie; Fogel, Marilyn; Bastida, Ricardo Oscar (Marine Mammal Science)
Risso’s dolphin, Grampus griseus, is a small cetacean distributed worldwide in temperate and tropical oceans (Baird 2009). The distribution of this species in Argentine waters is not clear but appears to be continuous (Bastida et al. 2007), and includes the northern coast of Tierra del Fuego. Twelve mass strandings and 13 single strandings have been reported for Tierra del Fuego (Goodall et al. 2008), however, mass strandings are generally considered uncommon for this species (Baird 2009). Grampus typically inhabit oceanic waters associated with slope break boundaries (water depths of ∼400–1,000 m), but normally dive to depths of <50 m with maximum dives times of 10–30 min (Baumgartner 1997, Olavarr´ıa et al. 2001, Canadas ˜ et al. 2002, Wells et al. 2009). Grampus are believed to forage on neritic and mesopelagic oceanic squids that make vertical movements to surface waters at night. Sighting records suggest that Grampus usually live in subgroups of ∼10– 30 animals (Baird 2009, Pereira 2008). Observations of captive animals and mass strandings indicate that cohesive subgroups may be composed of same sex and similar aged individuals (Baird 2009, Bearzi et al. 2010), and therefore sex- and age-related dietary preferences may result from this behavior (Cockcroft et al. 1993). Also, large aggregations of Grampus can occur in response to abundant but ephemeral pulses of productivity related to oceanographic fronts that attract their primary prey squid (Davis et al. 2002, Bearzi et al. 2010). As in other regions, Grampus have also been observed in inshore waters at specific times of the year in several areas of the southwestern South Atlantic, including central Patagonia (Reyes 2006) and Pen´ınsula Valdes (W ´ ursig and W ¨ ursig 1980; R. Bastida, personal observation). ¨ Sighting records suggest that this species may move seasonally between inshore and offshore waters (Best 2007). The ecology of Grampus in the southwestern South Atlantic has never been intensively studied. Little is known about its food habits, ...